Li Bai rides a celestial dolphin home - Sexton, Tom, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2018)
Poetry about Alaska, growing old, and more.--Provided by publisher.
Snowy Egret Rising -- By the St. Croix River -- Wachusett Reservoir -- Maids in Yellow -- Lake Utopia -- West of Rousses Point, New York -- Glen Nevis, Ontario -- Superior Pulp, LLC -- New Wawa, Ontario -- Elderly Couple Having Breakfast at a Truck Stop -- In Praise of Surgeons -- Crossing the Prairies -- Yellow-Headed Blackbirds at Dusk -- The Man Behind the Wheel, Fort Nelson, B.C. -- Alaska Highway Lodge, 1966 -- House Sparrows at Glenallen, Alaska -- Li Bai Wakes in Broad Pass -- Li Bai and the Magpie -- Magpie's Wife -- Li Bai Meets a Brown Bear -- The Brown Bear -- Trapper -- Li Bai Arrives at Wonder Lake -- Almost Fall -- The North Fork Wolves -- Li Bai Discovers Adolph Murie's Cabin -- Coal Creek -- Heaven's River -- Li Bai Rides a Celestial Dolphin Home -- The Brown Bear's Lament -- The Magpies Build a Nest in Honor of Li Bai -- Coda: -- Russian American Bells -- Russian Orthodox Priest -- Richardson Homestead -- Black-Capped Chickadee -- Paper Birch -- Christmas Wolves -- Rime Ice -- Making Applesauce on a Snowy Afternoon -- Common Merganser on a Winter Morning -- Snow Squall -- Snow-Blind Rivers -- Benediction -- Goldfinches at a Feeder -- Saw-Whet Owl in a Hemlock Tree -- A Magical Fox -- The Winter Sky -- Moonlight -- In Praise of Visible Things -- Basho -- Thinking of Basho While Walking at Dawn -- Greening -- In This the First Long Light of Spring -- At Delta Junction.
Keywords: Poetry